2020
DOI: 10.31925/farmacia.2020.3.25
|View full text |Cite
|
Sign up to set email alerts
|

THE REAL-WORLD COST AND EFFECTIVENESS STUDY OF TREATING mCRC WITH BEVACIZUMAB FOLLOWED BY CETUXIMAB OR PANITUMUMAB IN WT KRAS PATIENTS

Abstract: Targeted monoclonal antibodies bevacizumab, cetuximab and panitumumab are reimbursed in the Czech Republic in combination with chemotherapy or alone in metastatic colorectal cancer (mCRC). However, the high cost is a potentially limiting factor. The real-world costs and effectiveness of first line bevacizumab followed by cetuximab or panitumumab (EGFRi) were retrospectively assessed from the perspective of healthcare payer. Total 71 WT KRAS patients (56% men; median age 60.5 years) were evaluated between April… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…In fact, because regular screening has increased so much within the past 20-30 years, the death rate of CRC has been decreasing [9]. And of course, the decrease in death rate is also because of improved treatment options and targeted therapies [12]. Similarly, dietary and chemopreventive measures also play a role in decreasing the overall incidence of CRC [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, because regular screening has increased so much within the past 20-30 years, the death rate of CRC has been decreasing [9]. And of course, the decrease in death rate is also because of improved treatment options and targeted therapies [12]. Similarly, dietary and chemopreventive measures also play a role in decreasing the overall incidence of CRC [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Such a difference was mainly due to the higher cost of drugs in the FOLFOX6+Bevacizumab regimen group. The results of the studies by Sehnalova et al from the perspective of the healthcare providers (2020) 54 and Pathak et al (2018) 55 showed that the direct medical costs of the group taking Bevacizumab was higher than the one taking Cetuximab, mostly due to the costs of chemotherapy drugs. However, the results of Shida et al's study (2018) 38 from the public medical care viewpoint showed that the mFOLFOX6+Cetuximab treatment arm was more expensive than the other arms, which is contrary to the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous economic reviews of bevacizumab in patients with mCRC in the United States of America, the United Kingdom, Canada, Australia and Israel indicated a lack of cost-effectiveness [9,18,19], rGBM in Canada [28], mCC in the USA [46], and ovarian cancer in Canada and Belgium [3,35] and a systematic evaluation including ten countries reported that the costeffectiveness of bevacizumab in NSCLC was inconclusive [29]. High proportion of costs with targeted therapies as bevacizumab in the first line in Wild type Kirsten ras oncogene (WT KRAS) patients with mCRC could make the national health system unsustainable in some countries [44]. We found that most patients treated with bevacizumab were suffering of colorectal cancer (50.84%) and more than half were males (209, 59.54%).…”
Section: Direct Costs On Monthsmentioning
confidence: 99%